VD_FINDINFO Décision / 2019 / 421 vom 7. Mai 2019 - VD Tribunal cantonal (2019)
TRIBUNAL DES MESURES DE CONTRAINTE, FRAIS DE LA PROCÉDURE, INDEMNITÉEN GÉNÉRAL | 135 al. 2 CPP (CH), 422 al. 1 CPP (CH), 81 CPP (CH)